AB0696 Retention rates of adalimumab, etanercept, and infliximab as first- or second-line biotherapies for spondyloarthritis patients in daily practice in auvergne (france). (15th June 2017) - Soubrier, M; Castagné, B; Pereira, B; Fan, A; Frayssac, T; Couderc, M; Malochet-Guinamand, S; Mathieu, S; Tatar, Z; Tournadre, A; Dubost, J-J
Abstract : Background: The use of tumour necrosis factor alpha (TNF-α) inhibitors – or anti-TNFs – has considerably improved the treatment of spondyloarthritis (SpA). The first three of these available anti-TNFs (infliximab, adalimumab, and etanercept) are the most widely used in the treatment of SpA. Their efficacy and safety have been demonstrated in extensive randomised controlled trials (RCTs).Nevertheless, the randomized studies were of short duration and included a selected population that differed from patients treated in daily practice Objectives: To compare, in real-life settings, the retention rates of the initial anti-TNF treatment (etanercept [ETN], adalimumab [ADA], and infliximab [IFX]) used as first-line biotherapy for spondyloarthritis (SpA), and to evaluate treatment switches to another anti-TNF inhibitor in the event of treatment failure. Methods: Monocentric retrospective cohort including all SpA patients starting an initial anti-TNF therapy between 2001 and 2015. Results: Of the 249 SpA patients analysed (135 radiographic cases, 114 non-radiographic), 102 were given ETN, 62 ADA, and 85 IFX. In total, 103 discontinued treatment. The median retention duration was 69.7 months (17–$∞)$ (ETN: 55.4 [17.6–94.6], ADA 57.6 [13.9–∞], and IFX: not reached). Retention was longer for IFX compared with ETN (HR=0.62 [0.39–0.99]) but non-significant compared with ADA (HR: 0.91 [0.56–1.48]). The percentage of patients continuing treatment after 5 years was 47% for ETN, 46% for ADA, and 62% for IFX. In multivariate analysis, the predictive factors for retention were a low BASDAI score (HR: 1.02 [1.01–1.04]), high CRP levels (HR 0.98 [0.97–0.99]), the concomitant use of disease-modifying therapy (HR: 0.4 [0.21–0.75]), and radiographic SpA (HR: 1.5 [1.0–2.52]). In total, 61 patients switched to another anti-TNF therapy. No difference was observed among the three anti-TNF therapies with regard to the median retention duration, but the retention rate was higher in the event of treatment switches from one monoclonal antibody to another. Conclusions: The retention rate in SpA patients proved high, and retention for IFX was superior to that of ETN. Disclosure of Interest: None declared